Sturge-Weber syndrome: Updates in pathogenesis, diagnosis, and treatment - Chelsea B. Valery; Anne M. Comi (Wiley, 2023)
Abstract Objectives We summarize the current knowledge of Sturge-Weber syndrome (SWS) including genetic involvement, difficulties in diagnosis, symptoms caused by the vascular malformations, treatments, and future areas of research. Methods PubMed searches were completed between October and December of 2022 including the following search terms: Sturge-Weber neuroimaging, Sturge-Weber ocular involvement, Sturge-Weber G‐protein alpha q subunit (GNAQ), Sturge-Weber presymptomatic treatment, and Sturge-Weber quantitative EEG. Clinically relevant articles and case reports were reviewed and summarized, with emphasis placed on reports from the last 20 years. Results Literature suggests that early identification of brain involvement is essential for optimal medical care. Infants with a port‐wine birthmark on the forehead, temple, or eyelids are at risk for SWS brain and eye involvement. Neuroimaging findings include leptomeningeal enhancements, cortical calcifications, and brain atrophy, and diagnosis requires magnetic resonance imaging with and without contrast. Before 1 year of age, neuroimaging has low sensitivity and may underestimate the extent of involvement; imaging after 1 year of age is needed to exclude brain involvement. The most common underlying cause for SWS is a somatic mosaic mutation in GNAQ. Neurological symptoms include seizures, stroke or stroke‐like episodes, headaches, and cognitive deficits. Recommended treatment for SWS brain involvement includes aggressive seizure control with antiepileptic medications; low‐dose aspirin is also frequently but not universally utilized. Current literature suggests that children with SWS may benefit from presymptomatic treatment; further study of this approach is ongoing. Conclusions SWS is a rare neurovascular disorder usually signaled by a facial port‐wine birthmark. Early diagnosis and appropriate treatment may improve outcomes.